Investigating Difficulties Encountered by Iraqi EFL learners in Their Opening and Closing a Conversation - te'ema Al-atabi, Faris Kadhim; Saleh Albadri, Mohammed Abed (مجلة كلية التربية, 2021)
English language conversations, just like in any other languages, are governed by definite etiquettes for keeping the flow of the speech smoothly going on. Proper openings and closings ways of a conversation are good examples for having a conversation well-understood and tangible. University students, after a long period of studying English, are seen unable to (open) start or close(end) a conversation due to many reasons and difficulties they face in this regard .The present paper has tried to investigate these difficulties by selecting a sample from third year students at English department /University of Wassit to achieve the aims of the study by carrying out a diagnostic test. The results have showed that university students do face difficulties in opening and closing a conversation. These difficulties are attributed to many reasons regarding; the prescribed textbook, little exposure to authentic conversations, methods of teaching conversation, and the students' deficiencies in the speaking and unawareness of the structure of conversations .
Keywords: Investigating